Large Vaginal Varicosities in the Setting of Pregnancy without Known Hepatic or Vascular Risks: A Case Report and Review of the Literature - Mark Sueyoshi; Steven Clevenger; Elaine Hart (Case Reports in Obstetrics and Gynecology)
Pregnancy may cause the onset of vaginal or vulvar varicosities that may be a concern for hemorrhage risk during childbirth. A 38-year-old female G4P1112 at 34 weeks and 1 day was referred to an outpatient OB/Gyn clinic for evaluation of a large vaginal mass. The referring provider had concern for malignancy. Lesions of the vulva were biopsied and found to be benign. For two months prior to presentation, she was experiencing discomfort with walking, yellow vaginal discharge, and dysuria. Treatment with fluconazole showed no improvement. She denied any personal or family history of malignancies, varicosities, or hepatic issues. Past surgical history was significant for laparoscopic cholecystectomy and two cesarean sections. A large vaginal mass during pregnancy is a concern whether it is malignancy or large vaginal varicosities that may put the patient at risk of severe hemorrhage during childbirth. We concluded that the mass was large vaginal varicosities as there was no discernible etiology. A repeat cesarean section was recommended due to the risk of hemorrhage during childbirth. For long-term management, close observation postpartum was recommended. Spontaneous resolution is a potential outcome and this is what our patient experienced. Without an underlying etiology, supportive measures are the best options.